Filling the Gaps in Antagonist CCR5 Binding, a Retrospective and Perspective Analysis - Amerzhanova, Yerkezhan; Vangelista, Luca (Frontiers in Immunology, 2022)
The large number of pathologies that position CCR5 as a central molecular determinant substantiates the studies aimed at understanding receptor-ligand interactions, as well as the development of compounds that efficiently block this receptor. This perspective focuses on CCR5 antagonism as the preferred landscape for therapeutic intervention, thus the receptor active site occupancy by known antagonists of different origins is overviewed. CCL5 is a natural agonist ligand for CCR5 and an extensively studied scaffold for CCR5 antagonists production through chemokine N-terminus modification. A retrospective 3D modeling analysis on recently developed CCL5 mutants and their contribution to enhanced anti-HIV-1 activity is reported here. These results allow us to prospect the development of conceptually novel amino acid substitutions outside the CCL5 N-terminus hotspot. CCR5 interaction improvement in regions distal to the chemokine N-terminus, as well as the stabilization of the chemokine hydrophobic core are strategies that influence binding affinity and stability beyond the agonist/antagonist dualism. Furthermore, the development of allosteric antagonists topologically remote from the orthosteric site (e.g., intracellular or membrane-embedded) is an intriguing new avenue in GPCR druggability and thus a conceivable novel direction for CCR5 blockade. Ultimately, the three-dimensional structure elucidation of the interaction between various ligands and CCR5 helps illuminate the active site occupancy and mechanism of action.